LEGAL PROTECTION FOR WORKERS WITH DISABILITIES IN THE WORKPLACE TO ENSURE EQUALITY AND WELFARE IN INDONESIA - Manalu, Bryan Septian; Hadi, Syamsul (Awang Long Law Review, 2025)
This study explores the legal protections for workers with disabilities in Indonesia, highlighting the importance of ensuring equality, inclusivity, and welfare in the workplace. Despite existing laws that safeguard their rights, persons with disabilities still face discrimination, limited job opportunities, and inadequate workplace accommodations. Indonesia has ratified the United Nations Convention on the Rights of Persons with Disabilities (CRPD) and enacted Law Number 8 of 2016 on Persons with Disabilities and Law Number 13 of 2003 on Manpower. However, enforcement remains weak due to poor implementation, lack of supervision, and limited sanctions for non-compliance. Using a normative juridical research approach, this study employs legislative and conceptual methods to review relevant laws, regulations, and literature and assess their effectiveness. Results show that, although legal norms promote equal employment rights, practical challenges persist because of structural and cultural barriers. Institutions like the Disability Service Unit (ULD) and initiatives such as DNetwork play vital roles in improving accessibility and fostering inclusive employment. Additionally, some local inclusive enterprises in South Tangerang demonstrate how community efforts can empower persons with disabilities in the workforce. The study concludes that strong legal protections require not only comprehensive laws but also effective enforcement, cooperation between the government and the private sector, and ongoing public awareness campaigns to combat stigma. Developing inclusive employment policies and adaptable work environments is essential for achieving social justice and advancing the welfare and productivity of workers with disabilities in Indonesia.